Correlacion de glucosa basal y hemoglobina glicosilada en pacientes con diabetes mellitus” - Quipuscoa Lázaro, María Flor (2011)
The present study had a purpose determination of the correlation and relationship between the biochemical parameters, basal glucose and glycated hemoglobin (HbA1c) in patients whit diabetes mellitus. For that were determined and analyzed for basal glucose and glycated hemoglobin in 225 patients (120 males and 105 females). After the evaluation found that there is r = 0.67 and a coefficient of determination r2 = 0.452 (for regression). The equation for the determination of glycated hemoglobin considering the values of basal glucose is Y = 0.02X + 4336 (P <0.05). We conclude that there is a correlation between basal glucose and glycated hemoglobin